Simulation of Navigation Receiver for Ultra-Small Satellite - A. A. Spiridonov; D. V. Ushakov; V. A. Saechnikov (Приборы и методы измерений)
Currently, ultra-small satellite aresubjectstostringentrequirementsintermsoftheaccuracyof determining the position of the satellite in orbit, while the satellite is the subject to restrictions on mass, size and power consumption. The aim of this work is to simulate of navigation receiver operation for the ultra-small satellite with restrictions on energy consumption and computational resources.The operating conditions are considered and the requirements to the onboard navigation receiver for the ultra-small satellite are determined. The navigation receiver operation at the initial stage, performance testing, error detection, analysis of the reliability of the solution of the navigation-time determination problem are described.The structure of the design ballistics problems for orbit prediction of ultra-small spacecraft and navigation satellites, radio visibility intervals for GLONASS and GPS systems, parameters of navigation signals have been developed.The motion relative to the satellite systems GPS and GLONASS for a preliminary orbit of СubeBel-1 have been simulated. The Doppler dynamics of the GPS satellite signals in the receiver without restrictions on the relative speed for one day has been calculated. Radio visibility intervals for GPS and GLONASS satellites were calculated and optimal conditions for the cold start of the navigation receiver with a relative speed limit (Vr < 500 m/s) for 1 hour of operation both in separate and in joint operation on both systems were determined.To test the verification methods of the experimental data of the СubeBel-1 satellite, the operation of the navigation receiver of the Nsight satellite was studied according to the received telemetry from the beginning of its flight until the moment it entered stable operation.It is shown that the telemetry data of the navigation receiver at the testing stage had a significant error. After software correction, the navigation receiver worked steadily throughout the week of observation, the error of longitude and latitude measurements did not exceed 0.2 degrees.